Role of 5-hydroxytryptamine type 3 receptors in rat intestinal fluid and electrolyte secretion induced by cholera and Escherichia coli enterotoxins. Issue 3 (September 1995) - Mourad, F H; O'Donnell, L J; Dias, J A; Ogutu, E; Andre, E A; Turvill, J L; Farthing, M J
Abstract : Cholera toxin and Escherichia coli heat labile toxin (LT) induced intestinal secretion has in the past been attributed exclusively to an increase in intracellular cAMP whereas E coli heat stable toxin (ST) induced secretion is mediated through cGMP. Evidence is accumulating on the importance of 5-hydroxytryptamine (5-HT) in cholera toxin induced secretion, but its role in LT and ST is not well established. This study therefore investigated in vivo the effect of 5-HT3 receptor antagonist, granisetron, on intestinal fluid and electrolyte secretion induced by cholera toxin, LT, and ST. Granisetron (30, 75, 150, or 300 micrograms/kg) was given subcutaneously to adult male Wistar rats 90 minutes before instillation of 75 micrograms cholera toxin or 50 micrograms LT in isolated whole small intestine. In situ small intestinal perfusion was performed with an iso-osmotic plasma electrolyte solution (PES) to assess fluid movement. In a second group of animals, granisetron (300 micrograms/kg) was given subcutaneously and two hours later small intestinal perfusion with PES containing 200 micrograms/l ST was performed. Cholera toxin induced net fluid secretion (median -50.1 microliters/min/g (interquartile range -59.5 to -29.8)) was found to be dose dependently decreased or abolished by granisetron (plateau effect at 75 micrograms/kg: 18 (-7.8 to 28), p < 0.01). Granisetron in high dose (300 micrograms/kg), however, failed to prevent LT or ST induced secretion (-52 (-121 to -71) v -31 (-44 to -18), and (-39 (-49 to 17) v (-22 (-39 to -3)), respectively). Sodium and chloride movement paralleled that of fluid. In conclusion, these data show that 5-HT and 5-HT3 receptors play an important part in cholera toxin induced secretion but are not involved in E coli heat stable or heat labile toxin induced secretion.